Contemporary labor economics - McConnell, Campbell R. (McGraw-Hill Irwin, 2009)
Contemporary Labor Economics, 8e presents the "new" labor economics. In the past, study of labor was highly descriptive, emphasizing historical developments, facts, institutions, and legal considerations. Labor markets and unemployment was given some attention, but the analysis was typically minimal. This state of affairs has changed significantly in recent decades. Economists have achieved important breakthroughs in studying labor markets and problems. Labor economics is increasingly an applied field of micro and macro theory and has become a critical part of the core of analytical economics. As a result, the focus of the text is on the "new" labor economics. However, it also presents traditional topics such as labor law, structure of unions, and collective bargaining since these issues also play an important role in labor markets. In the Eighth Edition, the authors deliver new and updated discussions of public policy issues. Additionally, the text's integrated focus on global aspects of U.S. labor markets has continued and been expanded with this edition.